Semiotik Teoretiska tillämpningar i konstvetenskap 3 - Petersson, Sonya; Hedlin Hayden, Malin (Basic Readings in Culture and Aesthetics, 2022)
The anthology Theoretical applications in art science demonstrates, presents and problematizes the application of semiotic theory to art science study objects. The central ambition is to discuss and exemplify the specific questions and problems that semiotics' encounter with objects of study in art studies gives rise to. These include questions about visual communication and visual codes, materiality and mediality as well as in other contexts overlooked aspects of the sign, as well as the historicity of the sign and thus the interpretation. The anthology's six chapters include studies of contemporary fashion photography and sculpture, pre- and post-industrial furniture, 17th- and 19th-century oil painting, and 19th-century press images.